Interpreting Qur’anic Eschatology: Perspectives of Indonesian (Nusantara) Mufassirs - Hilma Alfathya; Andri Nirwana AN; Mohga Mohamed (Walidem Institute and Publishing, 2026)
Objective: This study aims to understand how Indonesian mufassirs interpret eschatological verses in the Qur'an, specifically regarding life after death, the apocalypse, and resurrection, and how these interpretations influence morality and behavior in the Indonesian context. Theoretical framework: The study is grounded in eschatology, focusing on the Islamic concepts of the afterlife and resurrection. It explores how different mufassirs interpret these themes and how their views affect Muslim beliefs and practices. Literature review: The literature review examines prior studies on Islamic eschatology and tafsir, highlighting the diversity of mufassir interpretations on eschatological verses. It also discusses the role of cultural and theological contexts in shaping these interpretations, with a focus on Indonesian perspectives. Methods: This research uses library research, analyzing books, tafsir texts, and related articles to compare the views of Indonesian mufassirs on eschatological themes, identifying key differences in their interpretations. Results: The study finds differing views among Indonesian mufassirs, such as Agus Mustofa’s belief that the afterlife is not eternal, and KH. Taufiqul Hakim’s affirmation of bodily resurrection reflects varied interpretations within the Indonesian context. Implications: The findings suggest the need for a more contextual approach in interpreting eschatological verses to avoid narrow or rigid readings and promote a deeper understanding of Islamic teachings in Indonesia. Novelty: This study offers a fresh perspective on Indonesian mufassirs’ views on eschatology, contributing new insights into Qur'anic interpretation within the Indonesian Islamic community.